Batteries Safety: Recent Progress and Current Challenges - Ould Ely, Teyeb; Kamzabek, Dana; Chakraborty, Dhritiman (Frontiers in Energy Research, 2019)
In this growing age of clean energy and the use of power storage to circumvent the use of traditional fossil fuel technologies, batteries of greater capacity, storage and power are increasingly becoming indispensable. New chemistries are being developed to increase the capacity of traditional lithium ion batteries and to develop batteries beyond Lithium ion. Promising high capacity cathodes and anodes are developed however their large-scale deployment is hindered due to safety concerns. In this review, we will summarize the state of the art of lithium ion batteries safety, highlight current challenges and outline the most advanced safety features that may be incorporated to improve battery safety for both lithium ion and batteries beyond lithium ion. Of particular interest is the issue of thermal runaway mitigation by incorporation of novel nano-materials and advanced technologies.